The Success of Shoot Cuttings of Pooti (Hopea gregaria Slooten) Applying Rootone-F - Faisal Danu Tuheteru; Asrianti Arif; NFN Husna; NFN Basrudin; NFN Albasri; NFN Danu; NFN Danar (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2020)
Pooti (Hopea gregaria Slooten) is a tree species of the Dipterocarpaceae. It is an endemic tree in Southeast Sulawesi and its existence is endangered. Flowering and fruiting periods of pooti is certainly unknown and do not produce fruits regularry which causes problem in generative propagation. One of the factors that influence the success of shoot cuttings is the presence of growth regulating substance, including the use of Rootone-F. The purpose of this study was to obtain the right dosage of growth regulators for the successful growth of pooti shoot cuttings. Design of the research was completely randomized design consisting of 8 concentrations of Rootone-F, i.e. (a) 0 ppm, (b) 50 ppm, (c) 75 ppm, (d) 100 ppm, (e) 125 ppm (f) 150 ppm, (g) 175 ppm and (h) 200 ppm. The result showed that Rootone-F treatment had not significant effect on all observed variables except for the number of secondary roots. Application of 200 ppm Rootone-F had significantly increased in secondary roots number of pooti shoot cuttings. Pooti plants are easily propagated by shoot cuttings without any treatment of Rootone-F.